Locally Fabricated Electronic Drum Trigger-Module - Julius Moises Albalos (Philippine Association of Institutions for Research, Inc., 2016)
Different electronic gadgets and devices nowadays exist and develop rapidly with the latest trends and technology. Gadgets have specific functions based on people's interests or needs in communication, transportation, music, and entertainment. The electronic drum is one of these gadgets that music enthusiasts would surely want to have. The study aimed to fabricate or assemble an electronic drum using raw materials which is locally available. The study used the experimental and project method. It was accomplished by fabricating the edrum module based on the circuit design of Admir Salahovic. The processes include the use of the toner transfer method in making the Printed Circuit Board; programming the microcontroller; the construction of the different triggers with the use of locally available materials and testing the device's functionality. The study concludes that the locally fabricated electronic drum trigger-module found on the internet as a do-it-yourself project using locally available materials works; it answers the queries of how electronic musical instrument works and what it is made of. The researcher and students are capable to build complicated electronic devices with the theories and skills learned behind it. It is recommended to enhance some of the trigger pads for a professional-like electronic drum kit.